3D‐printed custom ankle braces for people with Charcot‐Marie‐Tooth disease: A pilot study - Philps, Adam; Frecklington, Mike; Stewart, Sarah (Journal of foot and ankle research, 2024)
Introduction Charcot‐Marie‐Tooth disease (CMT) is a neurodegenerative condition resulting in footdrop, ankle instability and impaired balance and gait. This study aimed to determine (1) whether 3D‐printed custom ankle braces improve function and balance in people with CMT and (2) whether this is an acceptable device for use in this population. Methods A within‐subject comparison pragmatic/pilot study was undertaken. Ten people with CMT (mean [SD] age 48 [14] years, 60% male) were fitted with 3D‐printed ankle braces. Following a 4‐week wear‐in period, walking and balance tests and patient‐reported outcomes were assessed in two experimental conditions: (i) usual shoes and (ii) usual shoes with 3D‐printed custom ankle braces. Differences in outcome measures between experimental conditions were analysed using linear mixed models. Comfort, aesthetics and overall satisfaction of the brace were assessed via 100‐mm visual analogue scale (VAS). Adverse events and tripping/falls associated with the brace during the wear‐in period were also recorded by participants using daily diaries. Results A significant improvement was seen during single‐leg balance with eyes open (p = 0.026, Cohen's d = 0.55) and a significant reduction in foot pain (p = 0.045, Cohen's d = 0.82), with use of the ankle brace. Mean (SD) 100 mm VAS scores were 62.7 mm (17.9) for overall comfort and 73.9 mm (21.2) for overall satisfaction. Subjective data from the daily dairies showed that one participant found the brace too firm around the ankle due to loss of soft tissue mass and two participants found it challenging to don and doff the brace due to loss of hand dexterity. Conclusion This pilot study suggests that a 3D‐printed custom ankle brace may improve balance and reduce foot pain in people with CMT; however, larger‐scale trials are needed to further explore the impact of this brace on function and balance. Further customisation of the brace may also be required to improve acceptability for some people.